Pojęcie gospodarstwa rolnego według kodeksu cywilnego (rozważania na tle art. 55 3 k.c - Budzinowski, Roman (My University, 1991)
The article investigates the concept of agricultural real estate according to Art. 553 of the Civil Code. In particular, the author poses the question to what extent this concept corresponds with the requirements of modern agriculture. Three issues have been analysed in detail: the legal structure of an agricultural real estate, the basis of unity of components arranged into an agricultural real estate and the legal qualification and functions of particular material components of an agricultural real estate. The author concludes that the legislator does not treat an agricultural real estate as a unit of ownership only, but approaches this issue from the objective angle. For the time being, such an approach may be considered sufficient. However, in the future there may appear the neeed to pay more attention to functional aspects of an agricultural real estate, and thus the reference to the economic category of an agricultural real estate may prove necessary. At present, the concept of an agricultural productive unit assumes the presence of agricultural land. This is why the Civil Code provisions on agricultural real estates are not applicable to agricultural productive units that do not have such land. The author postulates to amend the Code provisions adequately.
The concept of agricultural real estate according to the civil code (art. 55 3)